Social sharing in LearnWeb2.0. (7th October 2009) - Marenzi, Ivana; Zerr, Sergej; Abel, Fabian; Nejdl, Wolfgang
Web 2.0 is a challenging environment, in which knowledge resources are distributed among heterogeneous online storage tools. Whereas each single Web 2.0 application is specialised in a set of predefined tasks (such as storing, editing or discussing specific types of resources), the integrated LearnWeb2.0 environment provides a rich set of functions and a seamless overview of the entire set of distributed knowledge resources. This paper describes the main functionalities for lifelong competence development of individuals in LearnWeb2.0, which we are developing within the TENCompetence project, motivated by a real world knowledge sharing scenario.